Desafios e perspectivas no enfrentamento da poluição marinha por plástico sob a ótica das negociações do acordo global juridicamente vinculante - Fernandes, Lucas Salles Gazeta Vieira (2024)
The present work aims to address the following research problem: what are the prospects for tackling marine plastic pollution from the perspective of negotiations on the globally legally binding agreement? Since the Industrial Revolution and World War II, there has been a significant increase in the annual production of plastic materials, which are now recognized as essential in various sectors. Global plastic use has quadrupled, primarily driven by emerging countries. This increase in plastic production is directly related to the rise in waste generation and its impacts on the planet, which are extremely harmful to global ecosystems if poorly managed. In this context, the marine environment becomes a focal point due to its transnational nature and the difficulties of managing and recovering the waste that has ended up there. The current international legal framework is insufficient to address the impacts of plastic waste and its harmful effects on the marine ecosystem, containing several gaps that hinder resolution. Thus, the United Nations Environment Programme (UNEP) decided to create a legally binding international instrument on plastic, which will be the first document to exclusively address plastic at an international level. This is the context of the study conducted. The research is exploratory, based on document analysis and bibliographic research, studying doctrines, legislations, scientific articles, and resolutions issued by international organizations and civil society research institutes. The study starts from the premise that, although existing international legal instruments have significantly contributed to mitigating marine plastic pollution, there is an urgent need for adaptations and improvements in the global normative framework. Therefrom, it concludes that the creation of a specific globally legally binding agreement on plastics, currently being negotiated under the auspices of UNEP, represents a significant advancement in this regard. Moreover, investments in infrastructure, technology, and capacity building, the promotion of a circular economy, and greater coordination among countries are essential to improve plastic waste management and effectively protect marine ecosystems. However, it is observed that the draft still faces considerable challenges. The multiplicity of options presented for each provision, often contradictory, reflects the complexity of the negotiations and the difficulty in reaching a global consensus. The presence of options allowing for flexibility or even the exclusion of important provisions raises concerns about the real effectiveness of the agreement in its final form.